Perbanyakan Pepaya (Carica papaya L.) ‘Sukma’ In Vitro dari Eksplan Tunas Pucuk sebagai Respon terhadap BA dan NAA - Wardani, Fitri Fatma; Efendi, Darda; Dinarti, Diny; Witono, dan Joko Ridho (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2019)
Papaya is one of tropical fruits native to Southern Mexico and which have been cultivated in Indonesia for a longtime. Papaya is usually propagated by seeds. Therefore, the offsprings are not true-to-type. This study was conducted todevelop a protocol of in vitro propagation of papaya ‘Sukma’ from shoot tips of in vitro germinated seeds as explants. Seedswere extracted from fruit that physiologically ripe and it germinated on MS basal medium. The experiment was set up in arandomized block design with culturing day as blocks (four blocks) and various concentrations of BA (0.0, 0.5, 1.0, 1.5, and2.0 mg L-1) in MS medium enriched with NAA 0.5 mg L-1 as treatment. Shoot tips in the MS medium without plant growthregulator as control so there was six treatments and 24 observation units. Each observation units contained five culturevessels and each culture vessels contained four explants. The results showed that the highest number of shoots, number ofleaves, number of nodes, and percentage of explant forming callus were obtained by BA 1.0-1.5, 1.0-2.0, 0.5-2.0, and 1.0-1.5 mg L-1, respectively. The highest percentage of explant forming roots were obtained in medium without BA. Analysis ofregression showed that the optimum concentration to get the highest number of shoots and leaves were BA 1.31 and 1.35 mgL-1, while explants will be rooted in medium without BA. Thus, in vitro propagation for papaya ‘Sukma’ should be conductedin two steps, i.e. for shooting and rooting growth.